2022
DOI: 10.1038/s41467-022-34571-4
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal delivery of a rationally attenuated SARS-CoV-2 is immunogenic and protective in Syrian hamsters

Abstract: Few live attenuated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines are in pre-clinical or clinical development. We seek to attenuate SARS-CoV-2 (isolate WA1/2020) by removing the polybasic insert within the spike protein and the open reading frames (ORFs) 6–8, and by introducing mutations that abolish non-structural protein 1 (Nsp1)-mediated toxicity. The derived virus (WA1-ΔPRRA-ΔORF6-8-Nsp1K164A/H165A) replicates to 100- to 1000-fold-lower titers than the ancestral virus and induces li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 64 publications
1
20
0
3
Order By: Relevance
“…Due to low concentrations, the hCoV-19/USA-WA1/2020 and hCoV-19/USA/MD-HP24556/2022 were further passed on Vero E6 cells after acquiring. Passaged viruses were deep sequenced to confirm 100% match with the original sequence 61 .…”
Section: Methodsmentioning
confidence: 99%
“…Due to low concentrations, the hCoV-19/USA-WA1/2020 and hCoV-19/USA/MD-HP24556/2022 were further passed on Vero E6 cells after acquiring. Passaged viruses were deep sequenced to confirm 100% match with the original sequence 61 .…”
Section: Methodsmentioning
confidence: 99%
“…Vaccinated individuals develop a specific adaptive cellular and humoral immunity against a wide variety of viral antigens at the systemic and mucosal levels. Besides, due to its similarity with the wild virus, it also stimulates innate immunity [ 109 , 152 , 153 , 154 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ]. Immunity induced by LAVs could allow the control of infections with new variants, avoiding severe infection symptoms and reducing the time of viral dispersal [ 109 , 149 , 167 , 168 ], leading to the reduction of new cases.…”
Section: Cellular and Humoral Immune Responses Induced By Sars-cov-2 ...mentioning
confidence: 99%
“…According to the observations on the vaccination with LAVs against SARS-CoV-2, in the direct recipients of the vaccine, it stimulates the components of innate immunity. Adaptive mucosal and systemic immunity is also developed against all the attenuated virus antigens, and this immunity confers resistance against the SARS-CoV-2 infection [ 159 , 160 , 161 , 162 , 164 , 165 , 166 , 167 , 168 , 169 ].…”
Section: Immunity Induced By the Indirect Acquisition Of Attenuated S...mentioning
confidence: 99%
“…In principle, transmission of a vaccine virus may contribute to the establishment of herd immunity, but there is a possibility that an attenuated virus may directly or through reversion to a more virulent form cause illness among some at-risk individuals. We have previously demonstrated the genome stability of Nsp1-K164A/H165A 23 . Here we found that the airborne transmission of Nsp1-K164A/H165A was less e cient compared to wild-type SARS-CoV-2 in hamsters, but most (except for one animal) sentinel hamsters became seroconverted after 14 days.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…1a) 22 . The resulted WA1-ΔPRRA-ΔORF6-8-Nsp1 K164A/H165A (abbreviated as Nsp1-K164A/H165A in this paper) is attenuated both in vitro and in vivo compared to wildtype virus and was immunogenic and protective against the ancestral SARS-CoV-2 challenge 23 . In the current study, we assessed the mucosal immunogenicity, e cacy in protecting diseases caused by recent variants of concern, as well as the transmission of a candidate attenuated SARS-CoV-2 vaccine.…”
Section: Introductionmentioning
confidence: 99%